Vostochnyĭ beregʺ poluostrova Kamchatki ot mysa Sīamo do mysa Zhupanova po opisi Gidrograficheskoĭ Ėkspedit︠s︡īi Vostochnago okeana 1919 godʺ / Chertilʺ Kapitanʺ mal. pl. Vishkarevʺ Kopirovalʺ Kapitanʺ mal. pl. Gragaĭtisʺ - Russia. Glavnoe gidrograficheskoe upravlenīe; (Vladivostok : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; Владивосток : [Морское министерство, Главное гидрографическое управленіе], 1919)
"Masshtabʺ 1/219156 ili 2609 s. (3 milʹ) v di︠u︡ĭmi︠e︡" = Scale 1/219156 or 2609 fathoms (3 miles) in 1 inch.; Title translation: Eastern coast of the Kamchatka Peninsula from Cape Siamo to Cape Zhupanova, according to the survey of the Hydrographic Expedition of the Eastern Ocean of 1919.; Relief shown by form lines, hachures and spot heights. Depths shown by soundings.; Includes table of coordinates.; Greenwich meridian Grayscale; 1:219,156